2014
DOI: 10.1891/1946-6560.5.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Couples Treatment for Intimate Partner Violence: Clients’ Reports of Changes During Therapy

Abstract: In 2005, 68% of the 50 states in the United States expressly prohibited the funding of any program that offers couples or family counseling when there has been intimate partner violence (IPV; Maiuro & Eberle, 2008). However, many couples experiencing violence want to participate in couples treatment. The purpose of this study is to examine the changes experienced by clients during participation in a couples treatment program for IPV. In this study, we analyzed interviews with couples participating in a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The couples-based approach again involves indirectly reducing IPV through couples' substance use treatment. In a qualitative analysis of interviews conducted with 14 couples who underwent the intervention, consistent themes emerged across male and female responses regarding safety as a primary treatment focus, increased feelings of safety during and after sessions, the incremental value of couples sessions over individual treatment, the importance of accepting responsibility for one's actions and committing to change [53].…”
Section: Couples Who Use Ipvmentioning
confidence: 97%
“…The couples-based approach again involves indirectly reducing IPV through couples' substance use treatment. In a qualitative analysis of interviews conducted with 14 couples who underwent the intervention, consistent themes emerged across male and female responses regarding safety as a primary treatment focus, increased feelings of safety during and after sessions, the incremental value of couples sessions over individual treatment, the importance of accepting responsibility for one's actions and committing to change [53].…”
Section: Couples Who Use Ipvmentioning
confidence: 97%
“…Quantitative results (Stith et al, ) indicate that completing the program, for both men and women, in both single couple and multi‐couple treatment led to reduced rates of physical violence toward their partners. Qualitative analyses from 14 couples who completed the program (Mendez, Horst, Stith, & McCollum, ) found that most men and women participating in the program reported individual and relationship changes. For example, one female client reported, “Well, in my relationship, we communicate better.…”
Section: Overview Of Dvfctmentioning
confidence: 99%
“…For example, one female client reported, “Well, in my relationship, we communicate better. We communicate more actually, and we understand” (Mendez et al, p. 32). One male client reported, “I thought that my option was the better one, the best one.…”
Section: Overview Of Dvfctmentioning
confidence: 99%
See 1 more Smart Citation